2011
DOI: 10.1002/ptr.3257
|View full text |Cite
|
Sign up to set email alerts
|

JAK2/STAT5 signaling pathway mediates Bojungbangdocktang enhanced hematopoiesis

Abstract: Bojungbangdocktang (BJBDT) is a medicinal herbal cocktail that has been used for cancer prevention and treatment in traditional Korean medicine. In the current study, BJBDT was demonstrated to regulate hematopoiesis. BJBDT significantly increased the expression of hematopoietic cytokines interleukin (IL)-3, stem cell factor (SCF), granulocyte-macrophage-colony stimulating factor (GM-CSF), thrombopoietin (TPO) and erythropoietin (EPO) at the level of mRNA and secretion in hematopoietic stem cells (HSCs). Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Jak2 is known to have an effect on myeloid progenitors [40,41]. Moreover, the Jak2 Stat5 pathway has been implicated in the development of progenitor cells by BJBDT [36] and TSPG [37]. Further investigation is required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jak2 is known to have an effect on myeloid progenitors [40,41]. Moreover, the Jak2 Stat5 pathway has been implicated in the development of progenitor cells by BJBDT [36] and TSPG [37]. Further investigation is required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of herbal samples have been shown to stimulate bone marrow progenitor cells, including polysaccharides from Angelica sinensis [35], a medicinal herbal cocktail Bojungbangdocktong (BJBDT) [36], a polysaccharide fraction from black soybean [36], and total saponins of Panax ginseng cells (TSPGs) [37]. We are the first to describe the stimulation of myelopoiesis activity by aerial parts of Echinacea species in female Sprague-Dawley rats [26].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the spectrum-effect relationship has been successfully applied to evaluate the bioactive material basis, with common data processing methods such as principal component analysis (PCA), canonical correlation analysis (CCA), gray correlation analysis (GRA), bivariate correlation analysis (BCA), and orthogonal partial least-squares regression analysis (OPLSR) [ 18 , 40 ]. Among them, the OPLSR method has high applicability when the datasets were small [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BD mouse model generated by 1-acetyl-2-phenylhydrazine (APH) coupled with cyclophosphamide (CTX) is commonly adopted to mimic the symptom of BD, such as weight loss, and decrease of blood routine indicators [ 12 – 15 ]. Therefore, blood routine indicators like HCT, HGB, and RBC were widely utilized to assess the blood tonic efficacy of drugs [ 16 – 18 ]. Besides, plant metabolomics enables the comprehensive comparison of the chemical constituents by combining the state-of-the-art high-resolution MS-based techniques with multivariate data analysis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bo-jung-bang-dock-tang (BJBDT) is a medicinal herbal cocktail that has been used for cancer prevention and treatment in traditional Korean medicine. Lim et al [44] suggested that BJBDT can enhance hematopoiesis via the hematopoietic cytokine-mediated JAK2/STAT5 pathway. BJBDT significantly increased expression of the hematopoietic cytokines interleukin (IL-3), stem cell factor (SCF), granulocyte-macrophage-colony stimulating factor (GM-CSF), thrombopoietin (TPO), and erythropoietin (EPO) at the level of mRNA and secretion in hematopoietic stem cells (HSCs).…”
Section: Hematopoietic Stem Cells In High-dose Chemotherapymentioning
confidence: 99%